2018
DOI: 10.4103/jfmpc.jfmpc_83_18
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechoic amniotic fluid in a term pregnancy

Abstract: The presence of highly echogenic amniotic fluid (AF) is uncommon, and presence creates a dilemma in the mind of the clinician. Echogenic AF has been attributed to meconium, blood, and vernix caseosa. Many studies have shown that the presence of meconium is unlikely in most cases. We report a case of highly echogenic AF detected at 37 weeks which was managed conservatively with careful fetal monitoring for further 2 weeks expecting spontaneous onset of labor. Labor was induced due to reduced fetal movements at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Such findings were in agreement with studies by Kandil et al 15 that There was no evidence of a link between prenatal lung echogenicity and liver maturity or newborn RDS.. The same research indicated thalamic echogenicity was found to be a reliable predictor of foetal lung maturity with a 77% and 79% for sensitivity and specificity, respectively and Keikhaie et al 14 study that the foetal intestine was divided into four phases. And Grade 4 foetal intestine was found to be a predictor of foetal lung maturity with a good specificity and a low sensitivity (62.5%) (98.9 percent).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such findings were in agreement with studies by Kandil et al 15 that There was no evidence of a link between prenatal lung echogenicity and liver maturity or newborn RDS.. The same research indicated thalamic echogenicity was found to be a reliable predictor of foetal lung maturity with a 77% and 79% for sensitivity and specificity, respectively and Keikhaie et al 14 study that the foetal intestine was divided into four phases. And Grade 4 foetal intestine was found to be a predictor of foetal lung maturity with a good specificity and a low sensitivity (62.5%) (98.9 percent).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies by Keikhaie et al and Sharma et al 14,26 indicated that grade III placenta was associated with good fetal pulmonary maturity and the absence of respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 89%